Management of Material Department of Organizations on the Basis of Automation Technologies - Tursinxanov N.; Pardayev M. (Research Parks Publishers, 2023)
In the current process of globalization, the development of information technology and artificial intelligence is leading to the rapid development of socio-economic processes. In this work, the mechanisms of automation of the process of management and monitoring of the department of material resources in organizations are presented. It provides an analysis of the effectiveness of automating the process of managing and monitoring the inventory department in organizations.